(untitled) (Journal of Partial Differential Equations, 2001)
A multiplicity result of a system of variational equalities, which is related to surfaces spanned over obstacles with prescribed mean curvature H, is obtained via a generalized Mountain Pass Lemma by proving a local compact result.